Introduction Teoksessa: Finland’s Famous Education System : Unvarnished Insights into Finnish Schooling - Thrupp Martin; Seppänen Piia; Kauko Jaakko; Kosunen Sonja (Springer, 2025)
Over recent decades, the Finnish education system has become regarded by many as the best in the world, generating international fascination. This introductory chapter begins by explaining that while many accounts have mainly set out to explain Finland’s success, this edited book seeks to offer a ‘warts and all’ account of education in Finland. Drawing especially on sociological and education policy perspectives, it covers diverse aspects of comprehensive schooling in Finland and is intent on addressing the challenges facing education in this Nordic country in a rigorous and balanced way. The chapter goes on to provide a general background to Finnish schooling and a description of the comprehensive school system. It looks at the place of Finland in global policy debates, considers debates about schooling that go on within Finland, and notes some of the concerns of Finnish educational researchers and scholars. Finally, this introduction also provides a brief overview of the chapters in this 28 chapter book.
Finland’s Famous Education System : Unvarnished Insights into Finnish Schooling